Judicial and Legal Reforms from 2016 to the Present Related to Improving the Procedural Status of Witnesses in Criminal Proceedings and the Increasing Significance of These Reforms (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Since 2016, Uzbekistan has undergone substantial judicial and legal reforms aimed at enhancing the criminal justice system. A key focus of these reforms has been the procedural status and protection of witnesses in criminal proceedings, historically a weak point due to gaps in legislation and the lack of effective safety guarantees. Prior to these reforms, the Criminal Procedure Code lacked provisions ensuring the safety, social support, and legal aid for witnesses, leaving them vulnerable to threats and unwilling to cooperate with investigative authorities. This article aims to analyze the development of legal measures and institutional mechanisms that strengthen the procedural status of witnesses through legislative innovation and international best practice adaptation. The analysis indicates the implementation of significant legislation, notably the 2019 Law “On the Protection of Victims, Witnesses, and Other Participants in Criminal Proceedings,” along with revisions to the Criminal Procedure Code that establish early testimony preservation and remote questioning procedures. Further developments include the integration of witness rights into the new Constitution and enhanced procedural guarantees for vulnerable groups, particularly minors. For the first time in Uzbekistan’s legal history, comprehensive procedural and social safeguards for witnesses have been consolidated, drawing from both national reform priorities and comparative international standards. These reforms signify a transformative step toward building a more just, secure, and rights-oriented criminal justice system. Continued research should assess the practical implementation and long-term impact of these legal changes on witness cooperation and crime investigation effectiveness.